2009
DOI: 10.1063/1.3200234
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ordering and spontaneous rotation of epitaxial habits in substrate-coherent InGaN and GaAsSb

Abstract: Coherently strained In0.5Ga0.5N on GaN and CaO substrates are theoretically predicted to show stable ordering in the chalcopyrite structure, as is Ga2AsSb on GaAs and InP substrates. Depending on the substrate and the film concentration, we predict a spontaneous rotation of the stablest chalcopyrite film axis from perpendicular to parallel to the (001) substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…It is well known from the literature that this type of ordering is energetically very favorable in the case of strained semiconductor alloys, not only nitrides. [52][53][54] Therefore, its appearance in our results is consistent with the previous findings. Moreover, the chalcopyrite pattern developed in our simulations is oriented perpendicularly to the substrate plane (CH ⊥ ) as predicted in the recent work of Liu and coworkers for large misfits.…”
Section: B Large Misfits Regimesupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known from the literature that this type of ordering is energetically very favorable in the case of strained semiconductor alloys, not only nitrides. [52][53][54] Therefore, its appearance in our results is consistent with the previous findings. Moreover, the chalcopyrite pattern developed in our simulations is oriented perpendicularly to the substrate plane (CH ⊥ ) as predicted in the recent work of Liu and coworkers for large misfits.…”
Section: B Large Misfits Regimesupporting
confidence: 93%
“…Moreover, the chalcopyrite pattern developed in our simulations is oriented perpendicularly to the substrate plane (CH ⊥ ) as predicted in the recent work of Liu and coworkers for large misfits. 54 The study of the remaining part of the concentration range reveals that the CH pattern is not the only ordering option. It turns out that different atomic arrangement occurs for the higher Ga concentration x > 0.7 .…”
Section: B Large Misfits Regimementioning
confidence: 99%
“…Liu et al 34,35 , have shown that GaAs 1-x Sb x ordered phases are stable in the entire region 0 1 x < < under epitaxial conditions. This is a result of the increased energy of the epitaxially strained GaSb that makes the phase separation unfavorable.…”
mentioning
confidence: 99%